2008
DOI: 10.5858/2008-132-1397-paccoo
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary and Cardiovascular Complications of Obesity: An Autopsy Study of 76 Obese Subjects

Abstract: Context.—Obesity is associated with sleep disordered breathing and cardiovascular morbidity, but the relationship between pulmonary hypertension, heart disease, and obesity is unknown. Objective.—To determine the prevalence of pulmonary and cardiovascular disease in obese subjects undergoing autopsy at a large medical center. Design.—A search through autopsy records from an 11-year period identified 76 subjects with a body mass index greater than 30 kg/m2 and 46 age-matched, nonob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…7 Interestingly, vascular proliferations in the form of PCH and glomeruloid structures, like those observed in our study, have been described in the lungs of morbid obese patients, a condition that predisposes to severe COVID-19. 8 However, in our series, we did not observe differences in weight between patients with different VS.…”
Section: Brief Communication Discussioncontrasting
confidence: 66%
“…7 Interestingly, vascular proliferations in the form of PCH and glomeruloid structures, like those observed in our study, have been described in the lungs of morbid obese patients, a condition that predisposes to severe COVID-19. 8 However, in our series, we did not observe differences in weight between patients with different VS.…”
Section: Brief Communication Discussioncontrasting
confidence: 66%
“…10 Retrospective review of autopsy records also showed that a significant proportion (44%) of obese individuals display medial thickening of the PAs, indicative of subclinical PAH. 10,11 These studies highlight an important link between excess body fat and pathological changes in the pulmonary circulation.…”
Section: Introductionmentioning
confidence: 98%
“…This is, in part, due to a lack of animal models that faithfully recapitulate features of HFpEF, 13 and a lack of understanding of the pathophysiology of RV dysfunction in the context of PH‐HFpEF. Given that obesity and metabolic syndrome are central to the pathogenesis of PH, RV dysfunction, and HFpEF, 8 , 23 , 24 our study validated and extended a relevant, obesity‐induced model of PH and HFpEF to study the pathogenesis of RV dysfunction in HFpEF. Exploiting common genetic variation among available mouse strains to account for effects of diet alone, we identified genes uniquely contributing to the development of RV dysfunction in the context of obesity‐induced PH‐HFpEF.…”
Section: Discussionmentioning
confidence: 85%